solve for:
9^x -5 x 3^x +6= 0
i've been trying to solve for this in which i have let U equal 3x and then by using the null factor law work out the answer. but somehow i didn't get the right answer :L
and also for:
Find the inverse function of
y=loge (x + 1) -2
in which i did
x= loge (y +1 ) -2
then x -2 = loge ( y+1)
but i seemed to get the wrong answer.
any help would be greatly appreciated!!
You're almost there after making the change shown in the quote. Solve this equation for y.Find the inverse function of
y=loge (x + 1) -2
in which i did
x= loge (y +1 ) -2
then x +2 = loge ( y+1)
but i seemed to get the wrong answer.
any help would be greatly appreciated!!